Mayaro Beach, Trinidad, B.W.I. - Sobrian, C. (Art Photo Studio, Trinidad, 2009)
A picture of a man standing facing the ocean while a small group walk along the beach. Boats have been beached under tall coconut trees which grow the entire length of Mayaro Beach. Postcard number 88702.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Mayaro; Beaches--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Coasts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Men--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Seashore--Trinidad and Tobago; Seaside architecture--Trinidad and Tobago